Penerapan Algoritma Apriori dalam Menentukan Pola Penjualan Produk Pertanian - Sirait, Wiranto Hernandesz; Saifullah, Saifullah; Jalaluddin, Jalaluddin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Agricultural products are an important component in agriculture. Agricultural products cover various types of needs in agriculture such as fertilizers, pesticides, and plant seeds. Good layout arrangement of goods in a store can increase time efficiency in terms of service to consumers and increase consumer buying interest in the store. Transaction data on sales of agricultural products owned by UD. Muara Tani has not been used properly by shop owners. The a priori algorithm is one of the methods found in data mining that is often used to find the occurrence/frequency of interconnected data patterns. The a priori algorithm can be used to find patterns of association relationships that exist in sales patterns. Based on calculations using the a priori algorithm, 5 association rules were formed with amount minimum of support 30% and minimum confidence 80%. That is, if you buy UREA agricultural products, you may also buy KCL, ZA, SP-36, NPK and LANNATE agricultural products